2021
DOI: 10.1097/olq.0000000000001537
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Vaginosis and Its Association With Incident Trichomonas vaginalis Infections: A Systematic Review and Meta-Analysis

Abstract: Background: Bacterial vaginosis (BV) has been associated with an increased risk for acquisition of human immunodeficiency virus and sexually transmitted infections. We evaluated the association between BV and incident Trichomonas vaginalis (TV) infection in women.Methods: MEDLINE and ClinicalTrials.gov were searched for articles published between January 1, 1980, and May 7, 2021. Observational studies in women that evaluated the relationship between having/not having BV and the risk for acquiring TV were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 73 publications
(415 reference statements)
0
7
0
1
Order By: Relevance
“…This study hinted that history of other vaginitis and history of HPV infection were risk factors for UBV, consistent with another study which showed that women with BV were twice as likely to acquire trichomonal vaginitis compared with women without BV. [22] Specially, when it comes to history of other vaginitis, there existed a signi cant statistical difference (P1 = 0.0088). Reproductive history and menstrual cycle had little effect on UBV, but one study found luteal phase to be a protective factor of BV [17].…”
Section: Discussionmentioning
confidence: 94%
“…This study hinted that history of other vaginitis and history of HPV infection were risk factors for UBV, consistent with another study which showed that women with BV were twice as likely to acquire trichomonal vaginitis compared with women without BV. [22] Specially, when it comes to history of other vaginitis, there existed a signi cant statistical difference (P1 = 0.0088). Reproductive history and menstrual cycle had little effect on UBV, but one study found luteal phase to be a protective factor of BV [17].…”
Section: Discussionmentioning
confidence: 94%
“…Our study is also the first to investigate EV-miRNAs differential expression in response to axenic P. bivia vaginal colonization and to contrast that to L. crispatus colonization. P. bivia is an abundant pathobiont of the vaginal microbiome community state CST-IV, subtype A [ 67 ], which presents BV-related characteristics, and a close to 2-fold increased risk of acquiring T. vaginalis infection [ 18 ]. Both pathogens, T. vaginalis and P. bivia , uphold clinical relevance associated with poor perinatal outcomes, urogenital cancer, and increased susceptibility to viral STIs [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of the cervical microbiome also ranked the L. crispatus -dominated CST as the least proinflammatory, and the P. bivia -dominated as the most proinflammatory, hence, pathogenic CST [ 13 ]. BV is linked with an increased risk of developing urogenital cancer, obstetric complications, and acquiring sexually transmitted infections (STIs) [ 6 ], including human papillomavirus (HPV) [ 14 , 15 ], human immunodeficiency virus (HIV) [ 16 , 17 ] and Trichomonas vaginalis ( T. vaginalis ) [ 18 ], the causative agent of trichomoniasis.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, Treponema pallidum has not been formally assessed in this context. By meta-analysis, microbiotas low in lactobacilli (by Nugent score, or sequencing, or inferred by Amsel criteria based BV diagnosis,) are associated with increased risk of HIV-1 [97,98,99], HPV [100 ▪▪ ,101] and C. trachomatis [100 ▪▪ ] by 1.5-fold and of T. vaginalis by almost 2-fold [102 ▪▪ ]. The evidence for N. gonorrhoeae and M. genitalium remains mixed [100 ▪▪ ].…”
Section: Genital Microbiota Influence Sexually-transmitted Infection ...mentioning
confidence: 99%